An unusual triad: Bilateral dilated odontoma, hypodontia and peg laterals - Alphy Alphonsa Sebastian; Auswaf Ahsan; Ahkin John George; John Aby (Wolters Kluwer Medknow Publications, 2013)
The dilated odontoma is an infrequent developmental alteration that appears in any area of the dental arches and can affect deciduous, permanent and supernumerary tooth. Dens invaginatus is a developmental anomaly resulting from invagination of a portion of crown forming within the enamel organ during odontogenesis. The most extreme form of dens invaginatus is known as dilated odontoma. The aim of this case report is to present a rare case of bilateral dilated odontoma affecting a microdontic permanent lateral incisor in a 30 year old female patient with hypodontia and peglateral teeth with its clinical, radiological and histological features, which has yet been not reported. Bilateral presence of dilated odontoma is not a common occurrence, although a single tooth involvement in each case has been reported in the literature.